Comparison of Outcomes of Creating Pneumoperitoneum via Supraumbilical versus Infraumbilical Incisions in Laparoscopic Procedures - Afzal, Anam; Ajaz, Fahad; Ghafoor, Muhammad Tariq (Indus Journal of Bioscience Research, 2025)
Objective: To compare the outcomes of pneumoperitoneum establishment via supraumbilical and infraumbilical incisions in laparoscopic surgery with respect to time for creation of pneumoperitoneum, postoperative complications, surgical site infection, analgesic use, pain score and port-site healing. Study Design: Randomize controlled trial. Place and Duration of the Study: Department of General Surgery, Sheikh Zayed Hospital, Rahim Yar Khan, from February 2025 to June 2025. Methodology: Eighty patients undergoing laparoscopic cholecystectomy, appendectomy and diagnostic laparoscopy were randomized into two groups after consent: Group A (supraumbilical incision) and group B (infraumbilical incision). Open (Hasson) technique was used to create the pneumoperitoneum. Operative and postoperative outcomes per group were documented and analyzed for statistical significance via SPSS version 26.0 and p-value ≤0.05 considered significant. Results: Although both groups were similar at baseline (p>0.05), the time needed to create pneumoperitoneum turned out noticeably shorter with the infraumbilical entry, roughly 146 seconds on average, compared with about 153 seconds for the supraumbilical approach (p=0.027). Pain levels after surgery, the need for analgesics, and rates of surgical site infection didn’t differ much between the two sets of patients (p>0.05). By the seventh postoperative day, wounds at the port sites looked better healed in the infraumbilical group (p=0.001). Complications overall were rare and roughly the same in both groups (p=0.688). Conclusion: Both supraumbilical and infraumbilical incisions are safe and effective for creating pneumoperitoneum. Although, the infraumbilical approach offers advantage relatively in that it took shorter time to access the abdomen and had superior port site healing, without increasing postoperative pain or complications